Improvement of Maintenance Management and Multiplication of Stingless Bee Colonies at Bangun Sejahtera Indonesia (BSI) Mandiri Beekepers - Simel Sowmen; Rusdimansyah Rusdimansyah; Zahlul Ikhsan (Warta Pengabdian Andalas, 2026)
This community service activity aims to enhance the capacity of beekeepers in colony management and methods for propagating galo-galo bee colonies within the Bangun Sejahtera Indonesia (BSI) honey bee cultivation group. The background to this activity is the high rate of extinction of partner galo-galo colonies. The high rate of colony collapse has a significant impact on the economy of beekeepers, a decline in their honey production, as well as ecological consequences in the surrounding area, including a decline in pollinators. The activity was carried out through training, which began with an information session on factors that support colony survival, such as sufficient plant vegetation, anticipation of predator attacks, and optimal colony maintenance management. The main achievement of this activity was that approximately 60% of the ten trap boxes installed during training were successfully colonized by new galo-galo colonies within four weeks. This result demonstrates that the training improved beekeepers’ knowledge and skills in caring for colonies and installing trap boxes, which directly increased the number of colonies owned by beekeepers. Additionally, the success of colony acquisition through trap boxes can reduce the felling of trees where galo-galo nest in the wild, one tree for one colony.